Animal by-products collagen and derived peptide, as important components of innovative sustainable food systems—a comprehensive review. Issue 31 (1st November 2022) - Cao, Changwei; Xiao, Zhichao; Ge, Changrong; Wu, Yinglong
Abstract: In 2020, the world's food crisis and health industry ushered into a real outbreak. On one side, there were natural disasters such as the novel coronavirus (2019-nCoV), desert locusts, floods, and droughts exacerbating the world food crisis, while on the other side, the social development and changes in lifestyles prompted the health industry to gradually shift from a traditional medical model to a new pattern of prevention, treatment, and nourishment. Therefore, this article reviews animal by-products collagen and derived peptide, as important components of innovative sustainable food systems. The review also considered the preparation, identification, and characterization of animal by-product collagen and collagen peptides as well as their impacts on the food system (including food processing, packaging, preservation, and functional foods). Finally, the application and research progress of animal by-product collagen and peptide in the food system along with the future development trend were discussed. This knowledge would be of great significance for a comprehensive understanding of animal by-product collagen and collagen peptides and would encourage the use of collagen in food processing, preservation, and functional foods.